PERLINDUNGAN HUKUM TERHADAP NASABAH ATAS PERBUATAN PIALANG SAHAM YANG TIDAK BERITIKAD BAIK - Amrizal Fahmy Fahmy; Bismar Nasution; Keizerina Devi; Mahmul Siregar (USU LAW JOURNAL, 2015)
ABSTRACT   Legal liability to investors in the stock brokerage stock market is a relationship that is based on contractual relationships. There are responsibilities that must be carried by such broker to sell or buy action based on orders from investors. It is primarily a stockbroker more passive than active in its responsibilities to investors. However, there are actions that can be activated if there is a stock broker it really needed investors. The forms of action were not acting in good faith from a stock broker to the investor is informed not act properly on certain information effects, not informed and deliberate disregard of the use of investor funds were made ​​without the knowledge of investors stockbroker. Given legal protection Law Number  8 of 1995 on Capital Markets and Regulation Number  01 / POJK / 2013 concerning Consumer Protection Financial Services Sector is a legal protection in the form of preventive and repressive.